A preliminary analysis for assessing intructor's pedagogical content knowledge in entrepreneurship - Sipon, Merhayati; Lope Pihie, Zaidatol Akmaliah; Abd Rahman, Fadzilah; Abdul Manaf, Umi Kalthom (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Currently, a graduate with good entrepreneurship skills were having greater advantage, much preferred by most industries and firms, compared to other graduate with low entrepreneurship’s skill. Yet, to be able to instill good entrepreneurship’s skill among graduate, student’s should be taught by teacher’s or instructor’s with a strong pedagogical content knowledge in entrepreneurship. This study was conducted to validate a 28 items of Entrepreneurship Pedagogical Content Knowledge scale (EPCK), adopted from the literature. The validation analysis was done using two approaches: the alpha cronbach reliability scale in SPSS and the confirmatory factor analysis (CFA) in structural equation modelling (SEM). A 222 sample was collected in this preliminary analysis from six community college students. The students need to give response to a 5 point Likert scale instrument which consists of four construct’s, namely i) subject matter knowledge in entrepreneurship (SMKE), ii) instructional representative and strategy in entrepreneurship (IRSE), iii) instructional objective and context in entrepreneurship (IOCE), and iv) knowledge of the student’s understanding of entrepreneurship (KSUE). After the confirmatory factor analysis was done, only 16 items showed satisfactory results. The final model of this EPCK was significant (p=. 012 at α =.05) (CMIN/DF = 1.348; TLI =.968; RMSEA =.040; and factor loading, (>.6). The EPCK scale was reliable (α = .898; and CR = .952), and valid (AVE = .5) to measure instructor’s pedagogical content knowledge in entrepreneurship.